Successful treatment of critical coronavirus disease 2019 in a patient with lung cancer concomitant with pembrolizumab‐induced arthritis by methylprednisolone, baricitinib, and remdesivir. Issue 7 (6th July 2021) - Oda, Naohiro; Miyoshi, Keiji; Morichika, Daisuke; Beika, Yuka; Taki, Takahiro; Mitani, Reo; Okada, Toshiaki; Takata, Ichiro
Abstract: COVID‐19 in cancer patients on immunosuppressive agents for the treatment of immune‐related adverse events of immune checkpoint inhibitors can rapidly deteriorate. The combination therapy with methylprednisolone, baricitinib, and remdesivir may be effective for critical COVID‐19, and further clinical trials are warranted.